A simple and efficient method for making site-directed mutants, deletions, and fusions of large DNA such as P1 and BAC clones. - Borén, J; Lee, I; Callow, M J; Rubin, E M; Innerarity, T L

(untitled) (Genome Research, 1996)
This study addresses two important technical problems: how to perform targeted alterations such as site-directed mutagenesis and deletions in large fragments of DNA and how to construct full-length genes from two partly overlapping bacterial artificial chromosome (BAC) plasmids. Given the size and the lack of convenient unique restriction sites in these large-insert bacterial clones, these are nontrivial tasks. Here we describe a simple and efficient protocol based on RecA-assisted restriction endonuclease (RARE) cleavage, a method that enables sequence-specific cleavage of genomic DNA. The same protocol has been used with minor modifications to introduce site-specific mutations into an apolipoprotein-B 90-kb P1 clone, to generate deletions in a 160-kb BAC, and to generate a 160-kb BAC containing the complete 92-kb gene for low-density lipoprotein-related protein-1 (LRP-1) from two smaller overlapping BACs ("BAC marriage").